EPID-06. QUANTIFYING THE POTENTIAL PUBLIC HEALTH IMPACT OF VARICELLA ZOSTER VIRUS (VZV) VACCINATION ON GLIOMA INCIDENCE. (9th November 2020) - Shen, Erica; Wallace, Alexander; Zhang, Chenan; Shannon, Callie; Ashley, David; Walsh, Kyle
Abstract: BACKGROUND: Varicella zoster virus (VZV) is a neurotropic a-herpesvirus that causes chickenpox and establishes latency in the dorsal root ganglion. Live attenuated VZV vaccine was approved for use in 1995, with the CDC estimating 95% of teens had been vaccinated in 2014. Prior epidemiological literature suggests an association between VZV infection and glioma risk. METHODS: We conducted a systematic review and meta-analysis of prior studies on the association between VZV infection and glioma risk. We also identified genetic instruments for VZV infection from prior GWAS and tested these for association with glioma risk in TCGA and GliomaScan (2244 cases, 4914 controls). RESULTS: In six previous studies, individuals with positive chickenpox history or anti-VZV IgG seropositivity had 1.8-fold lower odds of glioma (ORmeta =0.55, 95%Cl=0.39–0.77), with similar effects by grade. GWAS hits for personal history of chickenpox ( HLA-A Gly107 and rs9266089) and shingles ( HLA-AArg97, HLA-DRB1 PheSerHis13, rs2523591, rs41316748 and rs7047299) were not associated with glioma risk, nor were polygenic scores (P >0.05). DISCUSSION: Prior VZV infection is associated with reduced glioma risk and, based on analysis of genetic instruments, this appears to be an acquired protection caused by VZV infection rather than innate immunologic differences. VZV infection in known to elicit a broader antibody response than vaccination, but it is unknown whether VZV vaccination provides comparable protection against glioma. Because 89% of U.S. adults have had chickenpox, the "prevented fraction" of glioma due to chickenpox is 29% of annual incidence. If VZV vaccination confers an equivalent 1.8-fold reduction in glioma risk, this prevented fraction could increase to 32%. However, if VZV vaccination is less protective, it could decrease to just 2%. This potentially drastic increase in glioma incidence in coming decades merits mechanistic studies comparing the neuro-immunologic consequences of VZV vaccination versus chickenpox infection and warrants early public health attention.